"I can give you money but there is no use. The best thing I [can] give you is education." Negotiating Educational Migration and Gender in a Chinese Malaysian family. Issue 1 (1st December 2015) - Thimm, Viola
Abstract: Over the past two decades, Singapore has steadily become a popular destination for migrants. While the reasons for migrating to Singapore are many and contextual, labour and education have been the primary driving factors for attracting migrants from around the world to Singapore. Although a popular migrants' destination, education and migration policies in Singapore are often gendered, and are negotiated along and across other axes of identification and differentiation such as ethnicity and ideas of 'modernity'. This article analyses gendered educational migration from Malaysia to Singapore focusing particularly on how educational migration leads to female self-transformation. Specifically, I argue that social actors negotiate educational migration within their gendered family constellations. The article first contextualises the empirical material by illustrating socio-historical processes in Singapore and Malaysia. In the next sections, I discuss my ethnographic methods and examine a brief history of the state of research in gender and educational migration. In conclusion, I offer a significant contribution to the growing and important body of scholarship on gender and transnational families by illustrating how gender is negotiated in migration using the case of a single Chinese woman's migration journey to becoming a 'modern woman'.